Environmental risks for falls of elderly attended by the Family Health Strategy team - Iara Sescon Nogueira; Nayana Flor Ulbinski; André Estevam Jaques; Vanessa Denardi Antoniassi Baldissera (Rev Rene)
Objective: to analyze the environmental risk for falls among the elderly living in the area covered by a Family Health Strategy team. Methods: cross-sectional research, using, as a data source, 80 forms of environmental risk evaluation of elderly falls. The collected data were transcribed and organized in a computerized spreadsheet, using the Microsoft Excel® program, and analyzed using descriptive statistics. Results: most elderly’s households were classified as low risk for falls (56.3%) and showed at least one environmental risk (94.0%), being the most frequently found in the bathroom (47.5%), in stairs (46.2%), and associated to light (41.2%). Conclusion: environmental risks were observed in different places of the households, highlighting the bathroom, stairs, and little light in the room, most of them being classified as a low environmental risk for falls.